Effect of season and irrigation on the chemical composition of Aloysia triphylla essential oil - Sgarbossa, Jaqueline; Schmidt, Denise; Schwerz, Felipe; Schwerz, Luciano; Prochnow, Daiane; Otomar Caron, Braulio (Revista Ceres, 2025)
Aloysia triphylla is an aromatic plant used in several industrial sectors, owing to the chemical properties of its essential oil. Biosynthesis of organic compounds is influenced by the growth conditions. As such, temporal and spatial variation affect the chemical composition of essential oils. We hypothesized that: i) the chemical composition of A. triphylla essential oil is influenced by differences in irrigation and season; and ii) the major components of A. triphylla essential oil do not vary between treatment conditions. To test these hypotheses, we determined the chemical composition of A. triphylla essential oil as a function of four seasons crossed with four irrigation levels. A completely randomized experimental design with a randomized block in a 4 × 4 factorial scheme, representing the four seasons of the year (summer, autumn, winter, and spring) and four irrigation levels (50%, 75%, 100%, and 125% of the reference evapotranspiration), was used with four replicates. Our results show that the chemical composition of A. triphylla essential oil varied with the two study factors, of which season was the major factor. The highest concentrations of constituents classified as monoterpene and sesquiterpene were observed in the summer season, and the highest constituents of the other group of compounds were observed in winter. In addition, the major components of the essential oil were α-citral, limonene, and β-citral, and their levels were the highest during winter.